Metodología para el mantenimiento correctivo en el sellado de transformadores conectados a la red en la empresa Cens epm s.a (2021)
The objective of this degree work was to determine the appropriate methodology for the application in the corrective maintenance of the sealing of power transformers in oil connected to the network in the company CENS EPM S.A. Together with the activities pertinent to the corrective maintenance of the sealing, different procedures and useful processes are analyzed when performing a corrective maintenance in the sealing of the transformer. The topics that were investigated and studied prior to the analysis of preventive and corrective maintenance of sealed in a power transformer in oil, were the constituent elements of this class of transformer, together with the factors that cause a deterioration of its insulation and airtightness system since a good knowledge of these issues facilitates both the development and the application of the equipment maintenance program.